2015
DOI: 10.1063/1.4933075
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance in nanostructured Ag incorporated ZnS films

Abstract: Silver incorporated zinc sulfide thin films are prepared by RF magnetron sputtering technique and the influence of silver incorporation on the structural, optical and luminescence properties is analyzed using techniques like grazing incidence X-Ray diffraction (GIXRD), atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS), micro-Raman spectroscopy, UV-Vis spectroscopy and laser photoluminescence spectroscopy. XRD analysis presents hexagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 57 publications
4
10
0
Order By: Relevance
“…AFM 2D and 3D mages of a 2%, b 4%, c 6%, d 8% and e 10% Zn doped CdS thin films et al[27]. The reduction of the grain size with the increase of Zn dopant in CdS thin films is in good agreement with the XRD results.…”
supporting
confidence: 79%
“…AFM 2D and 3D mages of a 2%, b 4%, c 6%, d 8% and e 10% Zn doped CdS thin films et al[27]. The reduction of the grain size with the increase of Zn dopant in CdS thin films is in good agreement with the XRD results.…”
supporting
confidence: 79%
“…The presence of more sharp and well-defined Raman bands in the Z150 film compared to the Z120 and Z180 films indicates the enhanced crystalline nature of this film, as revealed in the XRD results. The intense Raman band at ~348 cm -1 can be assigned to the longitudinal optical (LO) phonon [7,8,32,33], and the medium intensity band ~266 cm -1 can be assigned to the transverse optical (TO) phonon [7,8,33]. The Raman bands at approximately 140 cm -1 and 171 cm -1 can be attributed to the disorderactivated, second-order acoustic phonons [7,8,34,35].…”
Section: Fig 1(a)-(d) Xrd Patterns Of the Zns Films Deposited On Quamentioning
confidence: 99%
“…ZnS thin films can be prepared using various techniques, such as sputtering [7][8][9][10][11], metal organic chemical vapor deposition [12], molecular beam epitaxy [13], atomic layer epitaxy [14], sol-gel [15] and pulsed laser deposition [16]. Among these techniques, radio frequency (RF) magnetron sputtering is a relatively simple and costeffective technique for the preparation of ZnS films [17].…”
Section: Introductionmentioning
confidence: 99%
“…Chalana et al . concluded that Ag could cause photocatalytic activity of the ZnS when exposed to visible light due to the surface plasmon resonance (SPR) effect. In another survey, graphene‐based compounds demonstrate high potentials in this respect because of variegated properties such as unique physicochemical, optical and electrical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Sivakumar et al (22) reported the proper performance of synthesized ZnS-Ag nanocomposite as a photocatalyst for the degradation of organic pollutants under visible light irradiation. Chalana et al (23) concluded that Ag could cause photocatalytic activity of the ZnS when exposed to visible light due to the surface plasmon resonance (SPR) effect. In another survey, graphene-based compounds demonstrate high potentials in this respect because of variegated properties such as unique physicochemical, optical and electrical properties (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%